Light Modulated Reversible "On‐Off" Transformation of Arylazoheteroarene Based Discotics in Nematic Organization. Issue 3 (22nd November 2022) - Kumar, Pravesh; Bala, Indu; De, Ritobrata; Kumar Pal, Santanu; Venkataramani, Sugumar
Abstract: Three benzene‐1, 3, 5‐tricarboxamide (BTA) core‐based molecular systems appended with phenylazo‐3, 5‐dimethylisoxazole photoswitches at the peripheral position through variable‐length alkoxy chains have been designed and synthesized. The supramolecular interactions of the mesogens provided discotic nematic liquid crystalline assembly as confirmed by polarized optical microscopy (POM) and X‐ray diffraction (XRD) studies. Spectroscopic studies confirmed the reversible photoswitching and excellent thermal stability of the photoswitched states in solution phase and thin film. Also, atomic force microscopic (AFM) and POM investigations demonstrated the morphological changes in the self‐assembly induced by the photoirradiation as monitored by the changes in the height profiles and optical appearance of the textures, respectively. Remarkably, the liquid crystalline discotic molecules showed reversible "on and off states" controlled by light at ambient temperature. Abstract : Photoswitchable mesogens : A series of reversibly photoswitchable C 3 ‐symmetric discotic liquid crystals have been made using a threefold phenylazo‐3, 5‐dimethylisoxazole tethered benzene‐1, 3, 5‐tricarboxamide (BTA) core. In a discotic nematic organization, they exhibit high thermal stability of metastable states, excellent reversibility in photoswitching, and robust light‐controlled mesomorphological changes.